Trudności zachodnich wypraw Belizariusza - Krupczyński, Piotr (Acta Universitatis Lodziensis. Folia Historica, 1981)
The three Belisarius campaigns to the west (to Africa in 533-534 and to Italy in 535-540 and 544-549) are the subject of this study. The basic problem of this dissertation limits itself into the questions: Why did each of these three campaigns of Belisarius present him more and more difficulties which in turn made him resign the position of the commander-in-chief during his second Italian campaign? The Introduction contains the outline of this study and it deals with the primary souroe i. e. Procopius’ works. In chapter first the author examines the attitude of the population in Africa and Italy (of Roman as well as barbarian origin) towards military and politioal operations of Belisarius. In chapter second he seeks an answer to the question what importance to the course of the campaigns had the relatione of Belisarius with the emperor and his court, with the officers cadre and the soldiers’ masses. The matter under discussion in the third chapter are the provision and transport difficulties with which Belisarius struggled duffing his western campaigns. The closing chapter contains conclusions from the whole study.